UCSD's Smarr Receives Kanai Award. (Computer (00189162), 2007)
The article reports that professor Larry Smarr of the University of California at San Diego received the 2006 IEEE Computer Society Tsutomu Kanai Award. The award acknowledges important contributions to state-of-the-art distributed computing systems. Smarr is one of the leading authorities on supercomputers in the U.S. He has previously served as director of the National Center for Supercomputing Applications at the University of Illinois at Urbana-Champaign. Smarr is also a Fellow of both the American Physical Society and the American Academy of Arts and Sciences.